Pancasila in Modern Indonesian Legal Reform: Addressing Current Cases and International Debates on Ideology and Law - M Akbar Hadiprabowo; Wasino Wasino; Edi Kurniawan (Journal of Law and Legal Reform)
Pancasila, the foundational ideology of Indonesia, remains a cornerstone of the nation’s legal and political frameworks. However, the application of Pancasila in modern legal reform faces significant challenges, particularly in addressing contemporary legal cases and navigating international debates on ideology and law. This study examines the dynamic interplay between Pancasila’s principles and Indonesia’s legal reform efforts, focusing on their relevance to pressing domestic and global issues. The urgency of this research arises from the increasing tension between Indonesia’s ideological commitments and the pressures of globalization, human rights norms, and transnational legal principles. This research contributes novelty by analyzing specific case studies that highlight the complexities of integrating Pancasila within modern legal practices. It also addresses critiques from international actors who question Indonesia’s adherence to global legal standards while maintaining ideological authenticity. Using a doctrinal and socio-legal approach, this study evaluates the role of Pancasila in shaping legal doctrines, court decisions, and legislative reforms in Indonesia. The findings reveal that while Pancasila provides a robust framework for addressing social justice and national unity, its interpretation and implementation often encounter inconsistencies and resistance. By critically engaging with international debates on ideology and law, this research offers practical insights for aligning Pancasila with evolving legal and societal demands. It serves as a valuable resource for policymakers, legal practitioners, and scholars in Indonesia and beyond, fostering a deeper understanding of the ideological foundations of legal reform.